Aggregation-induced emission by sequence-selective assembly of cyanolated distyrylbenzene in supramolecular DNA architectures. Issue 44 (12th May 2022) - Ucar, Hülya; Wagenknecht, Hans-Achim
Abstract : Cyanolated distyrylbenzene conjugated to 2′-deoxyuridine is a new building block for supramolecular DNA architectures combining aggregation-induced emission and sequence-selective binding. Abstract : Cyanolated distyrylbenzene conjugated to 2′-deoxyuridine is a new building block for supramolecular DNA architectures combining aggregation-induced emission and sequence-selective binding. A high number of binding sites at the DNA template are occupied by cyanolated distyrylbenzenes. Light can be harvested in this assembly and transferred to terminal Atto dyes. Mixed DNA architectures with perylene were programmed by the sequence of the DNA template.